PENGARUH KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG (Studi Empiris Pada Perusahaan Property dan Realestate Yang Terdaftar Bursa Efek Indonesia Periode 2017 - 2019) - Rahmat Yospan; Ahmad Junaidi (Bajang Institute, 2021)
This study aims to determine whether institutional ownership, company size and profitability have a simultaneous effect on debt policy. The research was conducted at property and real estate companies listed on the Indonesia Stock Exchange in 2017-2019. This study used a purposive sampling method, with the number of companies 27 x 3 years of research and a total sample of 81. The results of this study state that: Institutional ownership has no effect on debt policy, the significance value is 0.834, Profitability has a negative effect on debt policy, the significance value is 0.005. Company size has a positive and significant effect on debt policy, a significance value of 0.002. And with an Adjusted R Square value of 15.2%, conservatism is influenced by independent variables namely company size, leverage, and managerial ownership structure by 25.9%.